Responsiveness of Monetary Policy to Economic Uncertainty: Evidence from the ASEAN-5 Plus 3 Countries - Lim, Ee-Vern; Gan, Pei-Tha; Azila, Abdul Razak; Awadh Ahmed, Mohammed Gamal
A notable feature of empirical research on the monetary policy rule is that not many studies rely on the responsiveness of the monetary policy to the goals of the central bank. Policy responsiveness aligns with the appropriate relative weights placed on the goals following their priority. To overcome this shortcoming, this study uses open economy Taylor rule in economic uncertainty and examines its empirical validity based on a sample of ASEAN five plus three countries, including Indonesia, Malaysia, Philippines, Singapore, Thailand, South Korea, Japan, and China. By employing the autoregressive distributed lag (ARDL) model, this study examines the long-run and the short-run relationships between economic uncertainty (i.e. output uncertainty, inflation rate uncertainty, and exchange rate uncertainty) and monetary policy. Additionally, this study examines the responsiveness of monetary policy in economic uncertainty for goal-based performance measures. The findings provide some policy implications; (i) both in the long run and/or short run, the central bank should consider the policy variables (namely, output, inflation rate, and the exchange rate) underlying the premise of unforeseen future economic events in its monetary policy decision makings for the best economic outcomes, and (ii) the responsiveness of monetary policy to the central bank’s goals can serve as a benchmark (namely, the size of the weights in policy rule) in aligning smooth movements of the policy rate.